Treatment compliance at initial and maintenance therapy at gastroesophageal reflux disease - V. I. Simanenkov; S. V. Tikhonov; N. B. Lischuk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze treatment compliance at initial course and maintenance treatment by proton pump inhibitors at gastroesophageal reflux disease (GERD). Material and methods. Overall 84 GERD patients with took part in prospective study: 50 (59.5%) men and 34 (40.5%) women aged from 18 to 74 years. By results of esophagogastroduodenoscopy and morphological investigation of mucosal biopsies non-erosive reflux disease (NERD) was diagnosed in 32 (38.1%) patients, reflux esophagitis was found in 52 cases (61.9%). Total period of patients monitoring was 12 months at which patients made five visits to the research center: initial, through 1.5, 3, 6 and 12 months with filling in of questionnaires of Spielberger-Khanin, Beck, SF-36 and abridged multifactorial questionnaire of the personality (AMQP). Treatment compliance was established according to duration of study participation, along with that patients self-estimated it on 2, 3, 4 and 5 visits by Morisky-Green test and 5-score analog scales of pharmaceutical treatment compliance and lifestyle verification. The first visit patients underwent 1:1 randomization to the educational program devoted to reflux disease. Results. Of all patients 17.9% missed the second visit, the logistic regression analysis revealed no factors associated to the early low compliance; 38% of patients made all five visits for 12 months. The latter differed significantly from those who dropped out of the study at different stages: they had high number of chronic diseases (р